Supervisory Strategies to Overcome Teacher Resistance to the MATATAG Curriculum in Zone 1, DepEd Zambales - Bongar, Jonna M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Grounded on curriculum change theories anchored with the unfreezing, change, and refreezing as necessary stages in managing educational transitions and the important roles of individual beliefs, systemic support, and supervisory strategies in implementing curriculum reforms, this quantitative-descriptive study investigated the resistance encountered by teachers and the supervisory strategies employed by school heads during the implementation of the MATATAG Curriculum by assessing the extent of teacher resistance in various dimensions, evaluate the supervisory strategies used by school heads, and analyze the effectiveness of these strategies from the perspectives of teachers. This research utilized a validated survey questionnaire to gather data from 150 teachers and 62 school heads in selected public elementary schools whom majority of teacher-respondents were female early adults, serving for 6–10 years, held the rank of Teacher I, most were handling Grade I learners and had earned master’s units. On the other hand, most school heads were middle adults, serving as Head Teacher III with EdD units and supervising 6–10 teachers. Findings revealed that in terms of resistance, both groups agreed that teachers encountered challenges related to readiness, structural and cultural constraints, learning resources, and perceptions of the curriculum. Notably, school heads perceived these challenges more intensely, particularly in the areas of support, training, and resources. Significant differences in resistance were observed based on academic rank, highest educational attainment, age, and sex. Monitoring and assessment emerged as the most effective supervisory strategy, followed by professional development, emotional support, and collaborative communication.